2022
DOI: 10.1038/s41390-022-02295-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective therapies in the NICU in term infants: present and future

Abstract: Outcomes of neonatal encephalopathy (NE) have improved since the widespread implementation of therapeutic hypothermia (TH) in high-resource settings. While TH for NE in term and near-term infants has proven beneficial, 30–50% of infants with moderate-to-severe NE treated with TH still suffer death or significant impairments. There is therefore a critical need to find additional pharmacological and non-pharmacological interventions that improve the outcomes for these children. There are many potential candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 153 publications
0
22
0
Order By: Relevance
“…The observed success with hypothermia has quickened the pace of laboratory investigations to identify viable pharmacologic therapies to justify randomized clinical trials and, ultimately, combine them with hypothermia. 76 Implementation of hypothermia has led to the identification of components of supportive care that may affect early childhood outcomes (hypoglycemia and hyperglycemia, hypocarbia, and blood pressure support) and require prospective investigation. With the dissemination of hypothermia, comprehensive organizations such as HOPE for HIE (https://www.hopeforhie.org, accessed May 5, 2023) have emerged to provide support and resources for parents of affected neonates.…”
Section: Discussionmentioning
confidence: 99%
“…The observed success with hypothermia has quickened the pace of laboratory investigations to identify viable pharmacologic therapies to justify randomized clinical trials and, ultimately, combine them with hypothermia. 76 Implementation of hypothermia has led to the identification of components of supportive care that may affect early childhood outcomes (hypoglycemia and hyperglycemia, hypocarbia, and blood pressure support) and require prospective investigation. With the dissemination of hypothermia, comprehensive organizations such as HOPE for HIE (https://www.hopeforhie.org, accessed May 5, 2023) have emerged to provide support and resources for parents of affected neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic hypothermia is the only approved treatment for term infants with moderate to severe HIE and can improve survival and reduce disability when started within 6 h and continued for 72 h after injury [ 1 , 24 , 25 , 26 , 27 ]. Nevertheless, 30–50% of these infants treated with therapeutic hypothermia still die or experience significant disability [ 24 , 28 , 40 ]. A key finding of the present study was that all interneuron populations were protected with this standard clinical cooling protocol, suggesting that any persisting functional deficits in cooled infants may be unrelated to cortical interneuron survival.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, neuroprotective therapies that target the negative inflammatory actions contributing to newborn brain injury may offer added therapeutic benefit in newborns affected by HI and/or exposed to pro-inflammatory conditions that further augment the degree of cerebral injury. Indeed, recent research efforts have explored treatments that target the dysregulated immune response observed in perinatal brain injury with varying levels of success, as it is the case with agents such as erythropoietin, stem cells and melatonin (Molloy et al, 2022; Pedroza-Garcia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%